Impact of renin-angiotensin system blockade on the prognosis of acute coronary syndrome based on left ventricular ejection fraction - Raposeiras-Roubín, Sergio; Abu-Assi, Emad; Cespón-Fernández, María; Ibáñez, Borja; García-Ruiz, José Manuel; D'Ascenzo, Fabrizio; Simao Henriques, Jose Paulo; Saucedo, Jorge; Caneiro-Queija, Berenice; Cobas-Paz, Rafael; Muñoz-Pousa, Isabel; Wilton, Stephen B; et al. (Elsevier BV, 2020)
For patients with acute coronary syndrome (ACS) treated with percutaneous coronary intervention (PCI), it is unclear whether angiotensin-converting enzyme inhibitors (ACEI) or angiotensin receptor blockers (ARB) are associated with reduced mortality, particularly with preserved left ventricular ejection fraction (LVEF). The goal of this study was to determine the association between ACEI/ARB and mortality in ACS patients undergoing PCI, with and without reduced LVEF.